Kajian Literatur : Perlindungan Hukum Terhadap Korban Revenge Porn (International Forum of Researchers and Lecturers, 2024)
Gender inequality, sexual violence, domestic violence, trafficking in women, and wartime exploitation are some of the many human rights violations that occur. With the advancement of information technology and globalization, the use of violence has changed and evolved. Revenge pornography, also known as